FUNCTIONAL ASSESSMENT OF THE GAIT FOR THE PATIENT WITH A TOTAL HIP ENDOPROSTHESIS - Marius NECULĂEȘ (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2012)
The purpose of this study is to underline the importance of individualizing the rehabilitation treatment withingait rehabilitation and of using the re-education exercises for the support degree with the stabilometric platform. I haveconducted a prospective study on a total number of 57 patients with an indication for total hip arthroplasty. Thepatients were divided into two samples: study sample A, with 40 patients who completed a specialized rehabilitationprogram for a minimum of 30 days and control sample B, made of 17 patients with cu THA, but who did not followsuch a program. For the evaluation, I have used the pedometer Omron Walking Stayl Pro, which calculates the averagevelocity of motion, the distance, and the number of steps per time unit. The testing took 2 minutes per subject, itoccurred in the preoperative and postoperative stage, as well as 30 and 90 days after the intervention. The experimentalmethod used in gait rehabilitation for the THA patients was the proprioceptive re-education of the support at theplantar level with the help of the stabilometric platform GPS400; this method re-educates the degree of articulatoryload. The outcomes of this study statistically underline a better evolution of all parameters measured for the studysample compared to the witness sample. The final conclusion of this study emphasises on the fact that earlyintervention with therapeutic programs that include exercises with the stabilometric platform does lead to much moreeffective gait rehabilitation.